INCREASING OF THE TEACHERS SKILLS IN ASSESSING CHILDREN WITH SPECIAL NEEDS THROUGH GUIDED TRAINING - Mahdi, Arisul - (Jurnal Abdimas, 2020)
The assessment of children with special needs is still a dilemma in the everyday school’s life either form the teachers’ point of view to the pupils’ one and their parents’ too. This article aims to describe the form of assessment training for children with special needs given to special teachers and to find problems related to assessment of children with special needs. The training involved forty special teachers in West Sumatera, Indonesia who have experienced teaching special needs children. They were given material on the identification and assessment of children with special needs, how to prepare and make assessment instruments, how to make instructions for filling in assessment instruments, and how to carry out assessments of children with special needs. The results show that there is an increase in the ability of special teachers in making instruments and instructions for filling out assessment instruments. Especially assessment in children with visual impairment, hearing impairment, mental retardation and physical impairment. However, special teachers have problems in assessing children with specific language impairments or children with ADD or ADHD. They have difficulties in evaluating tests with free response items, essays and performance tests. The special teachers hope that if the assessment is carried out by involving various relevant teams, the assessment work of children with special needs will be more emphasis on the ability-based approach and characteristics of children with special needs.